Productivity and Economic Performance of Sali Rice under System of Rice Intensification and Integrated Crop Management as Influenced by Weed Management Practices - ISLAM, M.; NATH, L.K.; DAS, A.; SAMAJDAR, T. (Indian Journal of Hill Farming, 2015)
Rice productivity in North East India is low mainly due to poor agronomic practices and cultivation of local low yielding tall varieties. An intervention was made at Sibbari cluster of South Garo Hills district of Meghalaya during kharif 2010 and 2011 to evaluate the weed management practices for system of rice intensification (SRI) and integrated crop management (ICM) method of rice establishment for higher productivity and income. Results revealed that minimum weed density (6.05/m2), weed dry weight (10.15 g/m2) and higher weed control efficiency (64.15 %) was obtained under ICM as compared to conventional rice culture (CRC). Minimum weed density (3.03), weed dry weight (4.66 g/m2) and higher weed control efficiency (83.71%) was observed under hand weeding twice at 20 and 40 days after transplanting (DAT) . Significantly higher plant height, effective tillers/hill, panicle length, test weight and grain yield of rice was obtained under SRI methods (4.63 t/ha) which was at par with ICM (4.58 t/ha) but remained superior to CRC. Hand weeding twice at 20 and 40 DAT gave higher growth and yield attributes and grain yield of rice. SRI fetched higher gross return (Rs. 55,560/ha). SRI method recorded comparatively higher gross return (Rs. 55,560/ha), net return (Rs.34, 526/ha) than ICM and CRC. Hand weeding twice at 20 and 40 DAT gave maximum gross return (Rs. 54,480/ha) and net return (Rs. 34,526/ha), whereas, B: C ratio was highest under cono- weeding at 20 and hand weeding at 40 DAT (2.59).